Ensino da ortografia: uma proposta de trabalho reflexivo com o 7º ano do ensino fundamental - Romanino, Julhana Cella (2016)
This research presents a description and analysis of orthographic mistakes found in written productions from students of 7th grade of elementary school, with the aim of proposing activities that help them understand the writing operation in its standard variant. The issues regarding to orthographic writing have reported a superficial work of school in the understanding of the written code, the phonological awareness and the arbitrariness of the language. Students demonstrate a misunderstanding of the writing operation, transcribing their speech and registering dialectal marks. To achieve the objective proposed, we based the research in theoretical and mothodological assumptions of Applied Linguistics and in studies of authors such as: Cagliari (1998, 2007, 2009), Bortoni-Ricardo (2004, 2005, 2006, 2008), Oliveira ( 2005) and Morais (2007, 2010). We adopted the qualitative approach and the method of action research. Intending to understand the processes by which the student learn orthographic writing, after writing texts in different discursive genres, mistakes were identified and cataloged based on Oliveira (2005), to verify the occurrences and delimit the phenomena to be explored in Teaching Unit. Many mistakes were identified arising from the arbitrariness of the language and mistakes related to the presence of oral marks in writing. The teaching unit includes production and writing fixing activities, trying to describe how the student performs the understanding of the graphic language system. From reflections about speech and writing and its principles, reading and writing practices is intended to engage students in real situations of writing, to create na author´s position, taking the word in all its dimensions. We hope that this work could help in working with writing, specifically spelling in order to take the student to master the graphic code of the language and expand their language skills.